Customer Relationship Management (CRM) Strategies and Service Quality in Building Customer Loyalty: A Case Study of the Grab Application in Bojonegoro, East Java, Indonesia - Esti Nur Fadila; Reza Anggapratama; Dwi Irnawati (Journal of Management Studies and Development, 2026)
The expansion of application-based online transportation services has intensified competition across platforms at national and global levels, compelling companies to adopt strategies that foster long-term customer loyalty. This study examines the effects of CRM and service quality on customer loyalty toward Grab in Bojonegoro Regency, Indonesia. This study employs a quantitative approach using a survey method, in which data were collected through questionnaires distributed to Grab customers. The data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using the t-test, F-test, and the coefficient of determination (R²). The results indicate that CRM has a positive and significant effect on customer loyalty. Service quality is also found to have a positive and significant effect on customer loyalty. Furthermore, CRM and service quality simultaneously have a significant effect on Grab customer loyalty. The coefficient of determination indicates that CRM and service quality explain part of the variation in customer loyalty, while the remaining variation is influenced by other factors outside the research model. These findings underscore the importance of integrating CRM strategies and enhancing service quality in fostering customer loyalty within the online transportation industry. This study is expected to provide an empirical contribution to the development of service marketing management literature and serve as a practical reference for online transportation companies in designing sustainable customer retention strategies within both regional and global market contexts.